The impact of the COVID-19 pandemic on Canadian national team athletes` mental performance and mental health: The perspectives of mental performance consultants and mental health practitioners - Dithurbide, L.; Boudreault, V.; Durand-Bush, N.; MacLeod, L.; Gauthier, V. (Frontiers in Psychology, 2022)
The COVID-19 global pandemic has led to significant disruptions in the lives of high-performance athletes, including the postponement of the Tokyo Olympic and Paralympic Games, the cancellation of many international and national competitions, and drastic changes in athletes` daily training environment. The purpose of this research was to examine the interplay between the mental health and mental performance of Canadian national team athletes and the impact of the COVID-19 pandemic on these variables from the perspective of mental performance consultants and mental health practitioners. Twelve individuals working in these roles with national team athletes participated in focus groups and interviews during the second wave of the COVID-19 pandemic in Canada. Findings from the inductive reflexive thematic analysis revealed three main themes: (a) factors impacting athlete mental health (i.e., social and environmental, psychological, and public health restrictions), (b) consequences of COVID-19 for athletes (low mood symptoms, anxiety and stress symptoms, maladaptive behaviors, time for life outside of sport, rest, and recovery), and (c) impact of the pandemic on practitioners (roles, preparation and resources, gaps, and well-being). Interestingly, athletes with prior good mental performance skills were perceived to be more equipped to cope with challenges related to the pandemic, which concurrently seemed to facilitate good mental health throughout the pandemic. Furthermore, even though the pandemic had several debilitative consequences on athletes` mental health, it imposed a break from training and competition that allowed them to rest and enjoy their life outside of sport. Finally, participants discussed the need for more mental health resources and better access to practitioners supporting mental performance and mental health in the Canadian sport system.